Emerging role of baricitinib in dermatology practice: All we need to know! - Sunil Dogra; Shikha Shah; Ayush Sharma; Seema Chhabra; Tarun Narang (Wolters Kluwer Medknow Publications, 2023)
Baricitinib is a competitive inhibitor of the Janus Kinase family of non-receptor protein kinases, predominantly acting against JAK-1 and JAK-2 subtypes. By downregulating transcription of various pro-inflammatory cytokines, this drug has shown efficacy across various dermatoses. Approved for severe cases of alopecia areata and moderate-severe atopic dermatitis in adults, baricitinib is being increasingly tried across many other indications with promising results. It is prudent that dermatologists remain aware of boxed warnings and precautions with the use of this much-discussed molecule, including its infectious, thrombotic, cardiovascular, and malignant ramifications. Long-term data on the use of baricitinib in dermatological conditions are lacking and further research is warranted since most data on safety profile is extrapolated from its use in rheumatology. The present review aims to highlight the immunopathogenic mechanisms of JAK-1/2 blockade, approved and off-label uses in dermatology, along with a concise review of laboratory monitoring and the side-effect profile of baricitinib.